Flood '98 and BRAC - a case study on three slums in Dhanmandi area of Dhaka city - Rashid, Sabina; Halder, Shantana R (BRAC Research and Evaluation Division (RED), 2019)
This study is on Kathal Bagan, Bou Bazaar and Hazaribagh slums in Dhanmondi Area in Dhaka city of Bangladesh. It describes mainly the suffetings of the slum dwellers during floods, their coping strategy, the extent of damages caused by floods and BRAC's action on relief for them. In Kathal Bagan majority slum dwellers relocated to other places since this slum was 3-4 feet under water for t\lilo months. Those who did not leave in all three slums raised their beds with breaks. Some of them moved to the top of the roof of their house. Majority of slum dwellers lived in the rented houses. They mainly lost their personal goods. All of them had to cut their expenditure by cutting three to one rice meal a day due to loss of income, employment and increase in the price of food items and other necessities. Although they were suffering from hygiene and sanitation problems but everybody drank safe water. BRAC is the only organization from whom they got food, water purification tablets, health and other supports. With great difficulties they all managed to pay back the loan and savings installments.